Investigating Growth of Gold Nanorods by Simultaneous Small‐Angle X‐Ray and Neutron Scattering (Part. Part. Syst. Charact. 3/2022). (14th March 2022) - Zech, Tobias; Metwalli, Ezzeldin; Götz, Klaus; Schuldes, Isabel; Porcar, Lionel; Unruh, Tobias
Abstract : In article number 2100172, Unruh and co‐workers study the scattering signal of organic cetrimonium bromide (CTAB) structures and inorganic gold nanorods, which are measured and correlated directly by simultaneously impinging the same sample volume with X‐rays and neutrons. This way, the structure of the organic CTAB micelles and gold nanoparticle stabilization layer can be correlated directly with the size and polydispersity evolution of growing gold nanorods.